Palaeobotany and palynology of coprolites from the Late Triassic Chañares Formation of Argentina: implications for vegetation provinces and the diet of dicynodonts - Perez Loinaze, Valeria Susana; Vera, Ezequiel Ignacio; Fiorelli, Lucas Ernesto; Desojo, Julia Brenda (Palaeogeography, Palaeoclimatology, Palaeoecology)
The early Late Triassic Chañares Formation of Argentina contains one of the richest tetrapod-bearing assemblages of this age worldwide and is important for understanding the origin and early radiation of suchians, dinosauromorphs, and mammaliaforms. Here, we describe the fabric and microfossil content of herbivore coprolites produced by large kannemeyeriiform dicynodonts. Identified inclusions are dominated by fragmentary plant debris (wood, cuticles) with minor palynomorphs, the latter being of special significance as they represent the first palynological assemblage obtained for the formation. The palynological assemblage, which is dominated by bisaccate pollen grains, Alisporites and Platysaccus (Umkomasiales = Corystospermales), and minor striate pollen grains and fern spores, is characteristic of the Ipswich Phytogeographic Subprovince. Also present are Ovalipollis and Ellipsovelatisporites, which are typically absent in this phytogeographic subprovince (being characteristic elements of the Onslow Subprovince), but have been reported in the younger Ischigualasto Formation from the same basin. A statistical analysis of Triassic palynofloras across Gondwana results in a grouping containing the Ischigualasto and Chañares formations, with assemblages of East Antarctica, which together comprise a subprovince that is transitional between Ipswich and Onslow floras. The paleobotanical and palynological content of the coprolites also sheds light on the feeding behaviour of dicynodont producers, suggesting low-feeding habits and non-strict selectivity of the food source. Fil: Perez Loinaze, Valeria Susana. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Vera, Ezequiel Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina. ...